PROMOTION THROUGH SOCIAL MEDIA ON UWAIS COLLECTION IN BANDAR LAMPUNG - Evi Meidasari (Prosiding International conference on Information Technology and Business (ICITB), 2018)
The increasing online business in Indonesia is due to the increasingly widespread changes in consumer behavior and the increasing development of the internet. Based on data released by the Ministry of Communication and Informatics the number of internet users in Indonesia in 2017 reached 143.26 million people, equivalent to 54.68% of the total population of Indonesia. This number experienced an increase compared to 2016 of 10.56 million people based on survey results. Promotion through social media is one of the powerful tools used by online shop businesses, because with good, consistent and continuous promotion, the businesses offered to consumers as end users / users will be accepted so that consumers can continue to make transactions through social media. The research conducted is descriptive research that is by using the literature study method. Where library research is carried out by gathering relevant information, the data sources obtained are: observation, documentation, information, interviews, which are related to research. The incessant promotion carried out by Uwais Collection so far has made Uwais Collection increasingly known by the people of Lampung for the use of social networks, especially social media through Facebook and Instagram. because by utilizing social media as a promotional media it will make it easier for buyers to make online transactions where the phenomena that occur at the community level tend to like online purchases without the hassle of spending time such as conducting offline transactions.Keywords : Promotion, Social Media, Facebook, Instagram